Regionalisation of heat waves in southern South America - Suli, Solange (2023)
This study describes the climatological characteristics of regional heat waves (HWs) over southern South America (SSA) for the warm seasons (October–March) of 1979–2018 based on daily maximum temperature series from 131 weather stations. Clustering of stations with high co-occurrence of simultaneous HW days is employed to identify regional HW events over five homogeneous regions: northern, central-eastern and southern SSA regions, central Argentina, and central Chile. When all regions are considered, we find a mean frequency of ∼4 HWs per year. Transitional regions (northern SSA, central-eastern SSA and central Argentina) are characterised by longer, albeit less intense, HWs than the southernmost region (southern SSA), whereas central Chile events display the lowest duration, intensity and extension. By aggregating these single HW attributes into a combined severity index, a ranking of historical HWs has been obtained, with the March 1980 event standing as the most severe one of SSA. The assessment of long-term changes reveals significant increases in the frequency of regional HW days over central Argentina and central Chile only. Trends in HW characteristics are also region dependent, and the southernmost region is the only one where HW severity has increased significantly. We report similarities and differences in the synoptic circulation patterns associated with regional HW events. Southern SSA HWs have the most distinctive signatures, related to extratropical high-pressure systems blocking the westerly flow. In the remaining regions, HWs are associated with anomalies in the South Atlantic (northern SSA, central-eastern SSA and central Argentina) or South Pacific (central Chile) High, and the intensification of the northerly low-level flow by regional thermal lows and South American Low Level Jet events. Regional HWs often migrate from northern to central-eastern SSA and central Argentina, following the displacement/intensification of the South Atlantic High, which partially explains the similarity of their associated patterns.